The Role of Civic Society on e-Governance Adoption: Study on Village-owned Enterprise of Pangkah Wetan, Gresik Regency - Didied Poernawan Affandy; Eko Ganis Sukoharsono; Aulia Fuad Rahman; Zaki Baridwan (Jurnal Ekonomi dan Studi Pembangunan, 2025)
This paper aims to examine the role of civic society on e-governance adoption and to investigate factors that affect the performance of village-owned enterprise as well as the impact. This study is descriptive research using qualitative approach. Using in-depth interviews and direct observation to informants, the study maps some problems associated with the strategy of e-governance adoption on village-owned enterprise Pangkah Wetan.The case shows that the lack of civic society participation, which is typical across different organizations, does contribute to this problem. However, the main predicament lies with the fact that a good corporate governance principle is never explicitly prioritized in the organization’s information systems strategy. E-governance adoption should consider both technological innovation and organizational environment, including role of civic society. Neglecting one aspect poses the apparent danger that the implementation is unlikely to bring about benefit to the organization. This paper presents the case of a village-owned enterprise in adopting good corporate governance principles in developing rural economy. It is expected that this case will help substantiate an instance of good governance adoption in a village-owned enterprise and latecomer development, which might impact the operation and performance of a village-owned enterprise.